Annual report of the Women's Health Care Committee, Japan Society of Obstetrics and Gynecology, 2018. Issue 1 (11th September 2018) - Kitawaki, Jo; Kato, Kiyoko
Abstract: Since 2010, the Women's Health Care Committee has addressed important issues linked to women's quality of life. The five agendas this committee has engaged this academic year are: (i) clinical study of urinary complications in perinatal and postpartum women's health care; (ii) education on infectious diseases prophylaxis in obstetrics and gynecology in Japan; (iii) educational activities regarding management guidelines for a female athlete's health care; (iv) training program for women's healthcare advisers; and (v) pregnancy‐ and lactation‐associated osteoporosis (PLOP). The detailed activities of the five subcommittees are described herein. This report is based on the Japanese version of our annual report ( Acta Obst Gynaec Jpn 2018;70 : 1538–1546), which publicizes the activities of our committee.